Witaj!
Przedstaw w postaci jednej potęgi. Połącz wyrażenie ze wzorem, z którego korzystasz.
[tex]a) \ (6^{2})^{3}=6^{2 \cdot 3}=6^{6}\\\\Wzor: \ (a^{m})^{n}=a^{m \cdot n}[/tex]
[tex]b) \ 7^{9}:7^{4}=7^{9-4}=7^{5}\\\\Wzor: \ a^{m} :a^{n}=\frac{a^{m}}{a^{n}} =a^{m-n}[/tex]
[tex]c) \ 8^{6} \cdot 8^{7}=8^{6+7}=8^{13}\\\\Wzor: \ a^{m} \cdot a^{n} = a^{m+n}[/tex]
[tex]d) \ \frac{9^{8}}{9^{5}} =9^{8-5}=9^{3}\\\\Wzor: \ a^{m} :a^{n}=\frac{a^{m}}{a^{n}} =a^{m-n}[/tex]
[tex]e) \ 2^{5} \cdot 4^{5} = (2 \cdot 4)^{5}=8^{5}\\\\Wzor: \ a^{m} \cdot b^{m} = (a \cdot b)^{m}[/tex]
[tex]f) \ \frac{2^{5}}{3^{5}} = (2:3)^{5} = (\frac{2}{3} )^{5}\\\\Wzor: \ a^{m} : b^{m} = \frac{a^{m}}{b^{m}} = (a:b)^{m}[/tex]
[tex]g) \ 4^{3} : 5^{3} = (4:5)^{3} = ( \frac{4}{5} )^{3}\\\\Wzor: \ a^{m} : b^{m} = \frac{a^{m}}{b^{m}} = (a:b)^{m}[/tex]
Pozdrawiam!